Analisis Hukum Islam Terhadap Praktik Akad Istishna - Junaidy, Athailah; Yusriadi, Yusriadi (Department of Islamic Economic Law, Faculty of Sharia, Sultanah Nahrasiyah State Islamic University, Lhokseumawe, 2022)
This research is entitled